Selection of firewood in Monte Mozinho (NW Iberia) in the Late Antiquity: A question of function and availability - Vaz, Filipe Costa (2018)
Monte Mozinho (NW of Portugal) is a large Roman settlement occupied since the beginning of the era until the late 5th century BC which spans over an area of 20 ha. Beginning in 2008, the excavations were centered in a new, previously unknown area, sector A-2008, where several soil samples were collected in 3rd-4th century levels, in order to obtain relevant archaeobotanical data. This paper focuses on the charcoal analysis carried out in three different combustion structures and surrounding areas in this sector's compartment 1 and 3. In Compartment 1, in samples associated with a hearth, Castanea sativa was the dominant taxa identified, followed by Quercus deciduous, Leguminosae and Populus. In the west corner of the compartment, a high concentration of charcoals e unrelated with the previous structure e was also identified. The vast majority of the charcoal collected there were from Pinus pinaster. The results from Compartment 3 relate to its defining structure: a large oven. Even if the range of species is roughly the same as in the other compartment, its proportion, quantity and dendrological data were very different. Leguminosae fragments with strong ring curvatures make up the majority of the analysed material, followed by Quercus deciduous and Castanea sativa. The comparative analysis of the charred material from these contexts allowed the understanding of different selective usages of wooden resources related to the structures' typologies and purposes. In Compartment 1, the small concentration of charcoals was most likely associated with a single combustion event. The hearth in the same compartment was used as a structure where fires were frequently set. The charred content of Compartment 3's oven proved to correspond to its use as a food oven, as ethnographic data demonstrates that Leguminosae was the preferred firewood for such usages. Additionally, the extensive presence of Castanea sativa, namely throughout Compartment 1, allowed the discussion of its role in the regional Roman ecological and economical dynamics.